Space nanometer multilayer WS2 lubricating film and preparation method thereof

By adopting nano-multi-layer WS2 structure and soft metal doping technology in the space lubricating film, the problem that lubricating films in the prior art is difficult to bear long life, and the effects of high hardness, low friction coefficient and long wear-resistant life are achieved. Suitable for high-load space moving parts.

CN119162549AActive Publication Date: 2024-12-20LANZHOU INST OF PHYSICS CHINESE ACADEMY OF SPACE TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411151102.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2024-12-20
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

The existing space lubricating film is difficult to bear long life and harsh working conditions, especially under the needs of high load-bearing and long life applications, and it is difficult to meet the wear resistance and durability requirements of space moving parts.

Method used

Using nano-multi-layer WS2 lubricating film structure, including Ti transition layer, nano-Ti-MoS2/Ti-WS2 composite layer and Ag-Ti-WS2 doped layer, it is deposited through high-power magnetron sputtering technology, combining the nano-multi-layer structure and Soft metal doping enhances the hardness and toughness of the film, and improves density and film-based binding.

Benefits of technology

It significantly improves the toughness, hardness and friction performance of the film, reduces the friction coefficient, and extends the lubrication life. It is suitable for high load and long life space moving parts, showing excellent atmospheric and vacuum tribological properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162549A_ABST
    Figure CN119162549A_ABST
Patent Text Reader

Abstract

The invention relates to the field of surface engineering, in particular to a nano multi-layer WS2 lubricating film for space and a preparation method of the nano multi-layer WS2 lubricating film. The nanometer multilayer WS2 lubricating film for the space comprises a Ti transition layer, a nanometer Ti-MoS2 / Ti-WS2 composite layer and an Ag-Ti-WS2 doping layer. The Ti transition layer is deposited on the surface of the base body, and the thickness of the Ti transition layer is 80- The nano Ti-MoS2 / Ti-WS2 composite layer comprises a Ti-MoS2 layer and a Ti-WS2 layer, the Ti-MoS2 layer and the Ti-WS2 layer are sequentially and alternately deposited on the surface of the Ti transition layer, and the thickness of the composite layer is 200-300 nm; the Ag-Ti-WS2 doped layer is deposited on the surface of the nano Ti-MoS2 / Ti-WS2 composite layer, and the thickness of the Ag-Ti-WS2 doped layer is 500 to 1000 nm. The overall thickness of the nano multi-layer WS2 lubricating film for the space is 800-1500 nm, and the nano multi-layer WS2 lubricating film for the space is prepared by adopting a multi-high-power pulse magnetron sputtering technology. Through combination of the nano multilayer structure and the soft metal doped WS2 layer, soft metal doping and WS2 play a synergistic lubrication effect, the lubrication life of the WS2 film is greatly prolonged, and the WS2 film has excellent atmospheric and vacuum tribological properties and can be applied to spatial heavy-load long-life movable parts such as harmonic reducers, shafts and guide rods.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of surface engineering, and in particular to a nano multilayer WS2 lubricating film for space use and a preparation method thereof. Background Art

[0002] Active parts such as harmonic reducers, bearings and gears are the main supporting active parts of various transmission mechanisms and drive mechanisms in space. With the in-depth development of space technology, application requirements for high load-bearing, long life and miniaturization are put forward for active parts in space. When high requirements are placed on weight and size restrictions, surface treatment is an ideal choice.

[0003] Commonly used solid lubrication in space includes soft films and hard films. The materials of soft films include silver, gold, lead and molybdenum disulfide. Such materials have low shear strength and good toughness. They can easily form a transfer film under load and show excellent lubrication properties. The materials of hard films mainly include diamond-like carbon and some compound films, which have relatively low friction coefficients and excellent wear resistance. Both soft films and hard films play an important role in the lubrication and wear-resistant service conditions of space activity mechanisms according to their own characteristics. However, in response to the subsequent high-load and long-life application requirements, it is necessary to develop new types of wear-resistant lubricating films. Summary of the invention

[0004] In view of the defect that the space lubricating film in the prior art is difficult to withstand long life and harsh working conditions, the purpose of the present invention is to provide a nano-multilayer WS2 lubricating film for space and a preparation method thereof. The nano-multilayer structure design is adopted to enhance the hardness and toughness of the film, and the soft metal Ag doping is used to not only improve the density of the film, but also Ag and WS2 have a synergistic lubrication effect.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] In the first aspect, the present invention provides a nano multilayer WS2 lubricating film for space use, comprising: a Ti transition layer, a nano Ti-MoS2 / Ti-WS2 composite layer and an Ag-Ti-WS2 doping layer, wherein:

[0007] The Ti transition layer is deposited on the surface of the substrate, and the thickness of the Ti transition layer is 80-100 nm;

[0008] The nano Ti-MoS2 / Ti-WS2 composite layer includes n Ti-MoS2 layers and n Ti-WS2 layers, wherein the n Ti-MoS2 layers and the n Ti-WS2 layers are alternately deposited on the surface of the Ti transition layer, the number of n is 1 to 5, the n Ti-MoS2 layers are relatively close to the Ti transition layer, the n Ti-WS2 layers are relatively far away from the Ti transition layer, and the thickness of the nano Ti-MoS2 / Ti-WS2 composite layer is 200 to 300 nm;

[0009] The Ag-Ti-WS2 doping layer is deposited on the surface of the nano-Ti-MoS2 / Ti-WS2 composite layer, and the thickness of the Ag-Ti-WS2 doping layer is 500-1000nm;

[0010] The thickness of the space nano multilayer WS2 lubricating film is 800-1500 nm.

[0011] Furthermore, in terms of atomic percentage, the Ti content in each Ti-MoS2 layer is 8 to 10 at%, and the Ti content in each Ti-WS2 layer is 6 to 12 at%.

[0012] Furthermore, in terms of atomic percentage, the Ag content in the Ag-Ti-WS2 doping layer is 6 to 10 at%, and the Ti content is 3 to 6 at%.

[0013] Furthermore, the substrate is a metal substrate, preferably a 9Cr18, 30CrMnSi or 40CrNiMo substrate.

[0014] In a second aspect, the present invention provides a method for preparing a nano multilayer WS2 lubricating film for space use, comprising the following steps:

[0015] Step (1) substrate pretreatment;

[0016] Step (2) using high power magnetron sputtering technology to prepare a Ti transition layer on the surface of the substrate;

[0017] Step (3) adopts high power magnetron sputtering technology to prepare a nano-Ti-MoS2 / Ti-WS2 composite layer on the surface of the Ti transition layer;

[0018] Step (4) uses high-power magnetron sputtering technology to prepare an Ag-Ti-WS2 doped layer on the surface of the nano-Ti-MoS2 / Ti-WS2 composite layer.

[0019] Furthermore, in the step (2), the conditions of high-power magnetron sputtering are: using Ti target as cathode, argon as working gas, Ti target current of 1.0-2.0 kW, substrate bias voltage of -50 V to (-150 V), and deposition time of 8-5 min.

[0020] Furthermore, in the step (3), the conditions of high-power magnetron sputtering are: using Ti target, MoS2 target, and WS2 target as cathodes and argon as working gas; Ti-MoS2 and Ti-WS2 layers are deposited alternately in sequence; when depositing Ti-MoS2, the Ti target current is 0.8-1.0 kW, the MoS2 target current is 1.5-2.0 kW, the substrate bias is -50 V to (-150 V), and the deposition time is 2 to 3 min; when depositing Ti-WS2, the Ti target current is 1.0-1.5 kW, the WS2 target current is 1.5-2.0 kW, the substrate bias is -50 V to (-150 V), and the deposition time is 2 to 3 min.

[0021] Furthermore, in the step (4), the conditions for high-power magnetron sputtering are: Ti target, WS2 target, and Ag as cathodes, argon as working gas, Ti target current of 0.3 to 0.5 kW, Ag target current of 0.8 to 1.2 kW, WS2 target current of 1.5 to 2.0 kW, substrate bias of -50 V to (-150 V), and deposition time of 35 to 45 min.

[0022] Furthermore, in all steps, the purity of all targets is 99.9%.

[0023] The technical solution of the present invention has the following advantages:

[0024] The nano multilayer WS2 lubricating film for space provided by the present invention combines a nano multilayer structure with a soft metal doped WS2 layer. The nano multilayer structure has the advantages of crack deflection at the interface, crack tip passivation at the interface, and prevention of micro crack initiation and expansion caused by stress concentration, and has significant advantages in improving film toughness, hardness and film-base bonding strength. Soft metal doping can have a synergistic lubrication effect with WS2, greatly improving the lubrication life of the WS2 film. The film prepared by the present invention has a relatively high hardness, a low friction coefficient, a long wear-resistant life, and excellent atmospheric and vacuum tribological properties. It can be applied to heavy-duty and long-life movable parts in space such as harmonic reducers, shafts and guide rods.

[0025] The present invention adopts high-power pulsed magnetron sputtering technology to prepare nano multilayer WS2 lubricating film for space use. This technology has a high ionization rate and is conducive to improving the compactness of the film and the bonding strength of the film base. The method is simple and easy to control, and can be mass-produced on the surface of space moving parts, with strong engineering application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 Schematic diagram of the structure of a nano multilayer WS2 lubricating film for space use according to an embodiment of the present invention;

[0028] Figure 2 This is a cross-sectional morphology of a nano multilayer WS2 lubricating film for space use prepared in Example 1 of the present invention;

[0029] Figure 3 is a curve showing the change of atmospheric friction coefficient of the space nano multilayer WS2 lubricating film prepared in Example 1 of the present invention as a function of sliding time;

[0030] Figure 4 is a curve showing the change of the vacuum friction coefficient of the space nano multilayer WS2 lubricating film prepared in Example 1 of the present invention as a function of the sliding time;

[0031] Figure 5 This is a cross-sectional morphology of a nano multilayer WS2 lubricating film for space use prepared in Example 2 of the present invention;

[0032] Figure 6 is a curve showing the change of atmospheric friction coefficient of the space nano multilayer WS2 lubricating film prepared in Example 2 of the present invention as a function of sliding time;

[0033] Figure 7 This is a curve showing the change of the vacuum friction coefficient of the space nano-multilayer WS2 lubricating film prepared in Example 2 of the present invention as a function of the sliding time. DETAILED DESCRIPTION

[0034] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present application.

[0035] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequential order. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present application described here. In addition, the terms "including" and "having" and any of their variations are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device comprising a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0036] In the present application, the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "middle", "vertical", "horizontal", "lateral", "longitudinal" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings. These terms are mainly used to better describe the present application and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific orientation, or to be constructed and operated in a specific orientation.

[0037] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to specific circumstances.

[0038] In addition, the term "plurality" shall mean two or more.

[0039] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0040] The technical problem to be solved by the present invention is to overcome the problem that the existing space lubricating film is difficult to bear a large load and have a long service life under harsh working conditions. To this end, the embodiment of the present invention provides a nano multilayer WS2 lubricating film for space and a preparation method thereof.

[0041] See also Figure 1 The nano multilayer WS2 lubricating film structure for space provided by the embodiment of the present invention is as follows Figure 1As shown, it includes: a Ti transition layer, a nano Ti-MoS2 / Ti-WS2 composite layer and an Ag-Ti-WS2 doping layer. The Ti transition layer is deposited on the surface of the substrate, and the thickness of the Ti transition layer is 80-100nm; the nano Ti-MoS2 / Ti-WS2 composite layer includes at least one Ti-MoS2 layer and at least one Ti-WS2 layer, and the Ti-MoS2 layer and the Ti-WS2 layer are alternately deposited on the surface of the Ti transition layer, the Ti-MoS2 layer is relatively close to the Ti transition layer, and the Ti-WS2 layer is relatively far away from the Ti transition layer, and the thickness of the nano Ti-MoS2 / Ti-WS2 composite layer is 200-300nm; the Ag-Ti-WS2 doping layer is deposited on the surface of the nano Ti-MoS2 / Ti-WS2 composite layer, and the thickness of the Ag-Ti-WS2 doping layer is 500-1000nm. The overall thickness of the nano multilayer WS2 lubricating film for space use is 800-1500nm.

[0042] Furthermore, based on atomic percentage concentration, the Ti content in each Ti-MoS2 layer is 8-10at%, and the Ti content in each Ti-WS2 layer is 6-12at%; based on atomic percentage concentration, the Ag content in the Ag-Ti-WS2 doping layer is 6-10at%, and the Ti content is 3-6at%.

[0043] Furthermore, the substrate is a metal substrate, preferably a 9Cr18, 30CrMnSi or 40CrNiMo substrate.

[0044] The nano multilayer WS2 lubricating film for space provided in the embodiment of the present invention is prepared by high-power pulsed magnetron sputtering technology, has a high ionization rate, and is beneficial to improving the density of the film and the film-base bonding strength.

[0045] Example 1

[0046] This embodiment provides a method for preparing a nano multilayer WS2 lubricating film for space use, comprising the following steps:

[0047] Step (1) Substrate pretreatment

[0048] The 9Cr18 substrate was placed in petroleum ether, alcohol and acetone solutions in turn and ultrasonically cleaned for 5 min respectively. The 9Cr18 substrate was placed in a high-power pulsed magnetron sputtering chamber and evacuated. When the vacuum degree of the chamber was better than 3×10 -3 After Pa, the 9Cr18 substrate was etched and cleaned by using the Ar+ ion beam generated by the anode layer ion source. The chamber pressure was 0.5Pa, a -800V pulse bias was applied to the substrate, the anode layer ion beam source voltage was 1000V, and the cleaning time was 10min.

[0049] Step (2) using high power magnetron sputtering technology to prepare a Ti transition layer on the surface of the substrate;

[0050] The argon gas pressure was adjusted to 0.3 Pa, a -50 V DC bias was applied to the substrate, and high-power pulsed magnetron sputtering deposition was performed. The Ti target current was 1.0 kW, the deposition time was 8 min, the purity of the Ti target was 99.9%, and the thickness of the Ti transition layer was controlled to be 80 nm.

[0051] Step (3) using high power magnetron sputtering technology to prepare a nano-Ti-MoS2 / Ti-WS2 composite layer on the surface of the Ti transition layer

[0052] The argon gas pressure was adjusted to 0.3 Pa, a -50 V DC bias was applied to the substrate, the MoS2 target and the Ti target were turned on, the purity of the MoS2 target and the Ti target were both 99.9%, the Ti target current was 0.8 kW, the MoS2 target current was 1.5 kW, the deposition time was 3 min, and a Ti-MoS2 layer was deposited; then the MoS2 target was turned off, and the WS2 target was turned on, the purity of the WS2 target was 99.9%, the WS2 target current was 1.0 kW, and the deposition time was 3 min to deposit a Ti-WS2 layer; the cycle was repeated ten times until the thickness of the nano-Ti-MoS2 / Ti-WS2 composite layer was about 200 nm;

[0053] Step (4) using high power magnetron sputtering technology to prepare an Ag-Ti-WS2 doped layer on the surface of the nano-Ti-MoS2 / Ti-WS2 composite layer

[0054] Ti target and WS2 target, Ag as cathode, argon as working gas, high-power magnetron sputtering deposition was carried out. The purity of Ti target and WS2 target was 99.9%, the Ti target current was 0.3kW, the Ag target current was 0.8kW, the WS2 target current was 1.5kW, the deposition time was 35min, and the thickness of the Ag-Ti-WS2 doped layer was controlled to be 800nm.

[0055] The surface morphology of the nano multilayer WS2 lubricating film for space prepared in this embodiment was observed using a 200FEG field emission scanning electron microscope. Figure 2 As shown, the space nano-multilayer WS2 lubricating film prepared in this embodiment presents a multilayer structure.

[0056] The tribological properties of the nano multilayer WS2 lubricating film for space use prepared in this embodiment were tested using a large balloon-disc friction tester (Anton Paar). The test conditions were: the wear piece was a 9Cr18 steel ball with a diameter of Φ8 mm, the load was 5N, and the rotation speed was 1000r / min. The test results are shown in Figure 2. Figure 3As shown in the figure, the ordinate represents the friction coefficient and the abscissa represents the friction time. It can be seen from the figure that the average friction coefficient is less than 0.05 and the friction time is greater than 400min. According to the calculation of wear life by multiplying the speed by the friction time, it can be known that the wear life is ≥4×10 5 change.

[0057] The tribological properties of the space nano multilayer WS2 lubricating film prepared in this embodiment were tested using a vacuum ball-disc friction tester (Anton Paar). The test conditions were: the vacuum degree was better than 5×10 -3 Pa, the wear part is a 9Cr18 steel ball with a diameter of Φ8mm, the load is 5N, and the speed is 1000r / min. The test results are as follows Figure 4 As shown in the figure, the ordinate represents the friction coefficient and the abscissa represents the friction time. It can be seen from the figure that the average friction coefficient is less than 0.005 and the friction time is greater than 400min. According to the calculation of wear life by multiplying the speed by the friction time, it can be known that the wear life is ≥4×10 5 change.

[0058] Example 2

[0059] This embodiment provides a method for preparing a nano multilayer WS2 lubricating film for space use, comprising the following steps:

[0060] Step (1) Substrate pretreatment

[0061] The 9Cr18 substrate was placed in petroleum ether, alcohol and acetone solutions in turn and ultrasonically cleaned for 5 min respectively. The 9Cr18 substrate was placed in a high-power pulsed magnetron sputtering chamber and evacuated. When the vacuum degree of the chamber was better than 3×10 -3 After Pa, the Ar generated by the anode layer ion source + The 9Cr18 substrate was etched and cleaned by ion beam flow, the chamber pressure was 0.5Pa, -800V pulse bias was applied to the substrate, the anode layer ion beam source voltage was 1000V, and the cleaning time was 10min;

[0062] Step (2) using high power magnetron sputtering technology to prepare a Ti transition layer on the surface of the substrate;

[0063] The argon gas pressure was adjusted to 0.3 Pa, a -150 V DC bias was applied to the substrate, and high-power pulsed magnetron sputtering deposition was performed. The Ti target current was 2.0 kW, the deposition time was 5 min, the purity of the Ti target was 99.9%, and the thickness of the Ti transition layer was controlled to be 100 nm.

[0064] Step (3) using high power magnetron sputtering technology to prepare a nano-Ti-MoS2 / Ti-WS2 composite layer on the surface of the Ti transition layer

[0065] The argon gas pressure was adjusted to 0.3 Pa, a -50 V DC bias was applied to the substrate, the MoS2 target and the Ti target were turned on, the purity of the MoS2 target and the Ti target were both 99.9%, the Ti target current was 1.0 kW, the MoS2 target current was 2.0 kW, and the deposition time was 2 min to obtain a Ti-MoS2 layer; then the MoS2 target was turned off, and the WS2 target was turned on, the purity of the WS2 target was 99.9%, the WS2 target current was 1.5 kW, and the deposition time was 2 min to obtain a Ti-WS2 layer; the cycle was repeated ten times until the thickness of the nano-Ti-MoS2 / Ti-WS2 composite layer was about 300 nm;

[0066] Step (4) using high power magnetron sputtering technology to prepare an Ag-Ti-WS2 doped layer on the surface of the nano-Ti-MoS2 / Ti-WS2 composite layer

[0067] High-power magnetron sputtering deposition was carried out using Ti target and WS2 target, Ag as cathode and argon as working gas. The purity of Ti target and WS2 target was 99.9%, the Ti target current was 0.5kW, the Ag target current was 1.2kW, the WS2 target current was 2.0kW, the deposition time was 45min, and the thickness of the Ag-Ti-WS2 doped layer was controlled to be 1500nm.

[0068] The surface morphology of the nano multilayer WS2 lubricating film for space prepared in this embodiment was observed using a 200FEG field emission scanning electron microscope. Figure 5 As shown, the space nano-multilayer WS2 lubricating film prepared in this embodiment presents a multilayer structure.

[0069] The tribological properties of the nano multilayer WS2 lubricating film for space use prepared in this embodiment were tested using a large balloon-disc friction tester (Anton Paar). The test conditions were: the wear piece was a 9Cr18 steel ball with a diameter of Φ8 mm, the load was 5N, and the rotation speed was 1000r / min. The test results are shown in Figure 2. Figure 6 As shown in the figure, the ordinate represents the friction coefficient and the abscissa represents the friction time. It can be seen from the figure that the average friction coefficient is <0.05 and the friction time is greater than 400min. According to the calculation of wear life by multiplying the speed by the friction time, it can be known that the wear life is ≥4×10 5 change.

[0070] The tribological properties of the space nano multilayer WS2 lubricating film prepared in this embodiment were tested using a vacuum ball-disc friction tester (Anton Paar). The test conditions were: the vacuum degree was better than 5×10 -3 Pa, the wear part is a 9Cr18 steel ball with a diameter of Φ8mm, the load is 5N, and the speed is 1000r / min. The test results are as follows Figure 7As shown in the figure, the ordinate represents the friction coefficient and the abscissa represents the friction time. It can be seen from the figure that the average friction coefficient is <0.005 and the friction time is greater than 400min. According to the calculation of wear life by multiplying the speed by the friction time, it can be known that the wear life is ≥4×10 5 change.

[0071] Test example

[0072] The tribological properties of the nano multilayer WS2 lubricating film for space prepared in Example 1-2 were tested using a large balloon-disc friction tester (Anton Paar). The test conditions were: the wear piece was a 9Cr18 steel ball with a diameter of Φ8 mm, the load was 5N, and the rotation speed was 1000r / min. The test results are shown in Figure 2. Figure 3 and 6 As shown in the figure, the ordinate represents the friction coefficient and the abscissa represents the friction time. It can be seen from the figure that the average friction coefficient is <0.05 and the friction time is greater than 400min. According to the calculation of wear life by multiplying the speed by the friction time, it can be known that the wear life is ≥4×10 5 change.

[0073] The tribological properties of the space nano multilayer WS2 lubricating film prepared in Example 1-2 were tested using a vacuum ball-disc friction tester (Anton Paar). The test conditions were: the vacuum degree was better than 5×10 -3 Pa, the wear part is a 9Cr18 steel ball with a diameter of Φ8mm, the load is 5N, and the speed is 1000r / min. The test results are as follows Figure 4 and 7 As shown in the figure, the ordinate represents the friction coefficient and the abscissa represents the friction time. It can be seen from the figure that the average friction coefficient is less than 0.005 and the friction time is greater than 400min. According to the calculation of wear life by multiplying the speed by the friction time, it can be known that the wear life is ≥4×10 5 change.

[0074] In summary, the embodiment of the present invention combines a nano-multilayer structure with a soft metal-doped WS2 layer. The nano-multilayer structure has the advantages of crack deflection at the interface, crack tip passivation at the interface, and prevention of microcrack initiation and expansion caused by stress concentration. It has significant advantages in improving the toughness, hardness and film-base bonding strength of the film. Soft metal doping can have a synergistic lubrication effect with WS2, greatly improving the lubrication life of the WS2 film. The nano-multilayer WS2 lubricating film for space prepared by the embodiment of the present invention has a relatively high hardness, a low friction coefficient, and a long wear life. The average friction coefficient in the atmospheric environment is less than 0.05, the average friction coefficient in the vacuum environment is less than 0.005, and the wear life is ≥4×10 5It exhibits excellent tribological properties and can meet the needs of high-load and long-life lubrication in space. It can be applied to heavy-load and long-life moving parts in space such as harmonic reducers, shafts and guide rods.

[0075] The embodiment of the present invention adopts a high-power pulsed magnetron sputtering preparation method, which has a high ionization rate, is conducive to improving the compactness of the film and the film-base bonding strength. The preparation method is simple and easy to control, can achieve mass production, and has a strong engineering application prospect.

[0076] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A nano multilayer WS2 lubricating film for space use, characterized in that: include: Ti transition layer, nano-Ti-MoS2 / Ti-WS2 composite layer and Ag-Ti-WS2 doping layer, among which, The Ti transition layer is deposited on the surface of the substrate, and the thickness of the Ti transition layer is 80-100 nm; The nano Ti-MoS2 / Ti-WS2 composite layer includes n Ti-MoS2 layers and n Ti-WS2 layers, wherein the n Ti-MoS2 layers and the n Ti-WS2 layers are alternately deposited on the surface of the Ti transition layer, the number of n is 1 to 5, the n Ti-MoS2 layers are relatively close to the Ti transition layer, the n Ti-WS2 layers are relatively far away from the Ti transition layer, and the thickness of the nano Ti-MoS2 / Ti-WS2 composite layer is 200 to 300 nm; The Ag-Ti-WS2 doping layer is deposited on the surface of the nano-Ti-MoS2 / Ti-WS2 composite layer, and the thickness of the Ag-Ti-WS2 doping layer is 500-1000nm; The thickness of the space nano multilayer WS2 lubricating film is 800-1500 nm.

2. The space nano multilayer WS2 lubricating film according to claim 1, characterized in that: In terms of atomic percentage, the Ti content in each Ti-MoS2 layer is 8 to 10 at%, and the Ti content in each Ti-WS2 layer is 6 to 12 at%.

3. The nano multilayer WS2 lubricating film for space use according to claim 1, characterized in that: In terms of atomic percentage, the Ag content in the Ag-Ti-WS2 doping layer is 6-10 at%, and the Ti content is 3-6 at%.

4. The nano multilayer WS2 lubricating film for space use according to claim 1, characterized in that: The substrate is a metal substrate.

5. The method for preparing a nano-multilayer WS2 lubricating film for space use according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step (1) substrate pretreatment; Step (2) using high power magnetron sputtering technology to prepare a Ti transition layer on the surface of the substrate; Step (3) adopts high power magnetron sputtering technology to prepare a nano-Ti-MoS2 / Ti-WS2 composite layer on the surface of the Ti transition layer; Step (4) uses high-power magnetron sputtering technology to prepare an Ag-Ti-WS2 doped layer on the surface of the nano-Ti-MoS2 / Ti-WS2 composite layer.

6. The method for preparing a nano multilayer WS2 lubricating film for space use according to claim 5, characterized in that: In the step (2), the conditions of high-power magnetron sputtering are: using Ti target as cathode, argon as working gas, Ti target current of 1.0-2.0 kW, substrate bias voltage of -50 V to (-150 V), and deposition time of 8-5 min.

7. The method for preparing a nano-multilayer WS2 lubricating film for space use according to claim 5, characterized in that: In the step (3), the conditions of high-power magnetron sputtering are: using Ti target, MoS2 target and WS2 target as cathodes and argon as working gas; Ti-MoS2 and Ti-WS2 layers are deposited alternately in sequence; when depositing Ti-MoS2, the Ti target current is 0.8-1.0 kW, the MoS2 target current is 1.5-2.0 kW, the substrate bias is -50 V to (-150 V), and the deposition time is 2 to 3 min; when depositing Ti-WS2, the Ti target current is 1.0-1.5 kW, the WS2 target current is 1.5-2.0 kW, the substrate bias is -50 V to (-150 V), and the deposition time is 2 to 3 min.

8. The method for preparing a nano-multilayer WS2 lubricating film for space use according to claim 5, characterized in that: In the step (4), the conditions for high-power magnetron sputtering are: Ti target, WS2 target, and Ag as cathodes, argon as working gas, Ti target current of 0.3 to 0.5 kW, Ag target current of 0.8 to 1.2 kW, WS2 target current of 1.5 to 2.0 kW, substrate bias of -50 V to (-150 V), and deposition time of 35 to 45 min.

9. The method for preparing a nano multilayer WS2 lubricating film for space use according to claim 5, characterized in that: The purity of all targets was 99.9% in all steps.

Citation Information

Patent Citations

  • High-bonding-force solid lubricating film layer used in wide temperature range environment, and preparation method of solid lubricating film layer

    CN108977776A

  • Molybdenum nitride / molybdenum disulfide / silver ternary composite high-temperature solid lubricating film and preparation method thereof

    CN111455318A

  • High-temperature-resistant nano multilayer self-lubricating coating for die-casting pulling core and preparation method

    CN112501571A

  • Wear-resistant molybdenum disulfide-based composite film and preparation method thereof

    CN117626179A

  • Manufacturing method and structure of hard coatingswith lubrication properties

    KR1020050063463A